GEOPOLITICAL AND REGIONAL ANALYSIS OF THE ARMENIA-IRAN RELATIONS IN 1998-2008 - Kelbizadeh, Elnur (Revista Inclusiones, 2020)
Relations with the post-soviet countries, especially with the Caucasus republics became a special aspect of Iran’s foreign policy, after the collapse of the USSR. Robert Kocharian was elected president and officially began his duties on April 9, 1998. In the period of Robert Kocharian, Armenia’s relations with Iran had to be developed due to economic and geopolitical conditions. This article explores the dynamics of İran-Armenia relations in the context of regional security. The methodological basis of the research is the principles of the theory of realism. A number of theoretical and applied methods have been used to study the development of bilateral relations. Research has shown that in relations with Iran, the Armenian side was more interested in developing economic relation in 1998-2008 years. Iran tried to use Armenia’s opportunities to soften the economic consequences of the sanctions imposed by the US and some European states. Iran’s attempts to bring natural gas to Europe via Armenia did not take place due to Russia’s pressure on Armenia.